Muscle contractile characteristics: relationship to high-intensity exercise - Morris, M. G.; Dawes, H.; Howells, K.; Scott, O. M.; Cramp, M.; Izadi, H. (European Journal of Applied Physiology, 2010)
We investigated the relationship between muscle contractile characteristics, collected using percutaneous electrical stimulation, and high-intensity exercise performance. Seventeen participants performed a muscle performance test for the calculation of rate of torque development (RTD), rate of relaxation (RR1/2), rate of fatigue and fatigue resistance. On a second visit the participants completed a Wingate cycle ergometer test with peak power, mean power, fatigue index and fatigue rate calculated. The muscle fatigue index related significantly to the WAnT fatigue index and fatigue rate (p < 0.01). The change in rate of torque development was also related significantly to the fatigue rate (W/s) during the WAnT. Subjects displaying the greatest reduction in RTD had the greatest fatigue rate during the WAnT and greater fatigue during the electrical stimulation protocol. There were no significant relationships between peak (r 0.36; p > 0.01) or mean power (r -0.11, p > 0.01) with any of the muscle performance measures. These findings demonstrate that muscle contractile characteristics, elicited during standardised in vivo electrical stimulation, relate to performance during a Wingate anaerobic test. They suggest that muscle contraction characteristics play an important role in high-intensity exercise performance and indicate that electrical stimulation protocols can be a useful additional tool to explore muscle contraction characteristics in relation to exercise performance and trainability.